Correlation Between Protein, Calcium and Zinc Intake with Stunting in Children Age 3-5 Years Old in Gubeng, Mojo, Surabaya - Ayuning Tetirah Ramadhani; Widati Fatmaningrum; Roedi Irawan (Health Notions, 2019)
Stunting is a condition that occurs as the result of the disruption in the growth of height due to poor nutrition intake and nutrition status, repeated incidence of infection and inadequate psychosocial stimulation. In year 2017, the prevalence status for stunting incindence in Indonesia is categorized as high, reaching at 29,6%. This study was conducted to determine the correlation between nutritional intake of protein, calcium and zinc with the incidence of stunting. This study was an observational analytic research with a case control method, conducted to determine the correlation between exposure of risk factors and disease by comparing stunting groups with non-stunting groups. This study obtained a relation between depleted calcium intake and stunting incidence using the Fisher’s Exact test with a p value of 0.001 and odd ratio 0.056. A significant correlation of insufficient calcium intake with the incidence of stunting was found, yet there were no correlation between insufficient protein and zinc intake with the incidence of stunting. Keywords: stunting; protein; calcium; zinc